Downlink wireless resource allocation method of V2X based on wireless sensing assistance - Zhimin HE; Yuzhe LIN; Yujie CHENG; Shi YAN (Dianxin kexue)
In vehicle-to-everything, the high-speed distribution and sharing of perception and safety data is crucial to road safety.However, the instability of communication links caused by high-speed vehicle movement will make the existing communication resource allocation methods based on vehicle location information reporting no longer efficient.Therefore, a downlink wireless resource allocation method based on wireless sensing assistance of communication nodes was proposed.Firstly, a joint optimization problem of communication mode selection and wireless resource allocation under the orthogonality of communication and sensing resources was constructed.Then, a communication mode selection based on clustering by Delaunay triangulation and a resource allocation strategy based on improved graph coloring to improve the downlink throughput was proposed to solve the problem of construction.Finally, the impact of wireless sensing estimation error and the number of vehicles on the performance of the algorithm was simulated and analyzed.Simulation results show that compared with traditional methods, the proposed algorithm can obtain better downlink communication performance gain under the same proportion of sensing bandwidth resources, and can withstand the impact of larger sensing errors on performance.At the same time, the computational complexity of the proposed algorithm is lower and the network computing resources can be saved.